2016
DOI: 10.1177/0117196816640988
|View full text |Cite
|
Sign up to set email alerts
|

From students to permanent residents: The role of social networks in the immigration transition of Indians in New Zealand

Abstract: According to the New Zealand Ministry of Business, Innovation and Employment, India is now the largest source-country of migrants approved for residence in New Zealand under the Skilled Migrant Category. In this context, many Indian international students have transitioned to temporary work and permanent residence. Drawing on data from 18 interviews with former Indian international students who have since gained permanent residence in New Zealand, the paper examines how social capital in the form of social net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…However, lack of a connection with New Zealanders, confinement to co-national community silos, and a fear of making mistakes when communicating in English are major challenges to developing networks. New migrants do not have work experience in their host country, yet NZ requires this from its migrants before offering employment (Joseph, 2016;Kaur, 2019). Lack of NZ-based work experience was identified as a key employment challenge for SLMKWs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, lack of a connection with New Zealanders, confinement to co-national community silos, and a fear of making mistakes when communicating in English are major challenges to developing networks. New migrants do not have work experience in their host country, yet NZ requires this from its migrants before offering employment (Joseph, 2016;Kaur, 2019). Lack of NZ-based work experience was identified as a key employment challenge for SLMKWs.…”
Section: Discussionmentioning
confidence: 99%
“…Often minorities are stereotyped as outsiders who do not want to engage with the dominant majority (Lee & Rice, 2007). It was found that there are disadvantages to being with one's own community as this disconnects networking with the host country community (Joseph, 2016).…”
Section: Theme Two: Networking and Nz-based Referencesmentioning
confidence: 99%
“…Migrants generally rely on their ethno-linguistic and religious community for guidance and help (i.e. finance, job referrals, subsidized accommodation, childcare) (Joseph, 2016: 180).…”
Section: Negotiating Social Mobility and Class Positioningmentioning
confidence: 99%
“…The nature/types of migration are not always straightforward, and people (may) switch their status over time. For instance, international students (who are temporary migrants) can become immigrants by obtaining permanent residency in New Zealand, as were the cases for Ritu and Shinya (see also Joseph, 2016). Thus, in this paper, we are cautious to use these terms ‘migrants’ and ‘immigrants’ depending on the context.…”
mentioning
confidence: 98%